A Comparison of Species Biodiversity at Cattle Point, San Juan Island: 1971 - 2018 - Armos, Bailey; Owen, Veronica (My University, 2018)
Algal species at Cattle Point on San Juan Island, WA have been monitored and surveyed by Friday Harbor Labs since 1971. This resource of data presented the opportunity to examine Cattle Point’s algal species diversification over 47 years. The goal of this research was to examine the changing diversity as well as the zonation of the area over time. Through this paper, we examine differences in percent cover from 2006, 2008, 2013, and 2018 using the program PRIMER. A dendrogram and MDS plot of the Bray Curtis Similarity of the percent cover data was used to visually represent the data. According to the dendrogram, a group of zone 4 transects dominated by kelps were less than 10% similar to all the other transects. The percent cover data was then tested using ANISOM statistical methods. Zone 1 was found to be the most differentiated from all four zones. This result matched the data from the dendrogram and MDS plot. No conclusions could be drawn from the ANISOM results on comparing the years due to different sampling methods. Using data from 1971-3, 2008, 2013, and 2018, presence/absence data of 49 species were examined. The number of species present increased and peaked in 1973 and 2008 and declined moving forward to 2018. Lastly, the change in percent cover of Fucus distichus was examined and found to be in overall decline. From all of these results, a lowering level of Fucus distichus as well as biodiversity was seen over time.
Completed for the class: Friday Harbor Laboratories Marine Botany 446, Summer 2018
Keywords: transects; Cattle Point; algae; zonation; biodiversity